Development of a Multifunctional Edible Coating and Its Preservation Effect on Sturgeon (Acipenser baeri♀× Acipenser schrenckii♂) Fillets during Refrigerated Storage at 4 °C - Chunming Tan; De Pang; Ruiyun Wu; Fanglei Zou; Bo Zhang; Nan Shang; Pinglan Li (Foods, 2022)
Although many coatings and films can improve the quality and shelf life of fish fillets during refrigerated storage, a more multifunctional coating material is needed. In this study, an edible alginate/protein-based coating solution was prepared by incorporating antimicrobial agents. The coating properties were characterized and its effects on the quality and shelf life of sturgeon fillets during refrigeration (4 °C) were investigated. Compared with sodium alginate coating (2% sodium alginate + antibacterial agents, H), the composite coatings (2% sodium alginate + antibacterial agents + 1:15 or 1:10 protein solution, HP-15 and HP-10) exhibited a more stable structure and better light, gas, and water barrier properties, and showed better quality-preservation effects on sturgeon fillets. The composite coatings treatments, especially HP-10 composite coating, exhibited significant (p < 0.05) effects in inhibiting microbial growth, maintaining sensory quality, reducing the production of total volatile basic nitrogen (TVB-N), decreasing nucleotide breakdown, and delaying the lipid oxidation and protein degradation in fillets. These findings confirm that the composite coatings can be used as a multifunctional coating material for freshness preservation of sturgeon fillets to improve quality and extend shelf life.